UJI EFEKTIFITAS DAUN PANDAN WANGI (PANDANUS AMARYLLIFOIUM ROXB) SEBAGAI ANTIJAMUR TERHADAP PITYSPORUM OVALE - siregar, Saadah; Topia, Riana (Jurnal FARMASIMED (JFM), 2021)
The Pandan Wangi leaf plant is a plant that belongs to the Pandanaceae family. The metabolite content of fragrant pandan leaves (Pandanus amaryllifolius Roxb.) Alkaloids, flavonoids, saponins, tannins are known to have an antifungal effect. Pityrosporum ovale is a yeast or single-celled fungus that belongs to the genus Malassezia sp, and belongs to the Cryptococcaceae family. Pityrosporum ovale causes superficial dermatomycosis which affects the stratum corneum in the epidermis layer. This fungus is a normal flora on the scalp, but in conditions of hair with excess oil glands, this fungus can thrive. The purpose of this study was to determine the inhibition zone of fragrant pandanus leaves (Pandanus amaryllifolius Roxb.) Concentrations of 10%, 20%, 30%, and 40% of Pytirosporum ovale on Potato Dextrose Agar media by diffusion method using disc paper. The diffusion method was used to measure the diameter of the zone of inhibition against fungal growth. The positive control used was ketoconazole 2% and negative control DMSO 1%. The results of the study using the diameter of the inhibition zone at a concentration of 10% were 7.86 mm, the inhibition zone at a concentration of 20% was 8.53 mm, the inhibition zone at a concentration of 30% was 8.76 mm, and the inhibition zone at a concentration of 40% was 9, 43 mm.